RECQ4 selectively recognizes Holliday junctions - Sedlackova, Hana; Cechova, Barbora; Mlcouskova, Jarmila; Krejci, Lumir (DNA repair, 2015)
The RECQ4 protein belongs to the RecQ helicase family, which plays crucial roles in genome maintenance. Mutations in the RECQ4 gene are associated with three insidious hereditary disorders: Rothmund-Thomson, Baller-Gerold, and RAPADILINO syndromes. These syndromes are characterized by growth deficiency, radial ray defects, red rashes, and higher predisposition to malignancy, especially osteosarcomas. Within the RecQ family, RECQ4 is the least characterized, and its role in DNA replication and repair remains unknown. We have identified several DNA binding sites within RECQ4. Two are located at the N-terminus and one is located within the conserved helicase domain. N-terminal domains probably cooperate with one another and promote the strong annealing activity of RECQ4. Surprisingly, the region spanning 322-400aa shows a very high affinity for branched DNA substrates, especially Holliday junctions. This study demonstrates biochemical activities of RECQ4 that could be involved in genome maintenance and suggest its possible role in processing replication and recombination intermediates.
Keywords: replikace DNA; multimerizace proteinu; DNA Replication; sekvence nukleotidů; helikasy RecQ; DNA, Cruciform; vazebná místa; terciární struktura proteinů; Base Sequence; křížová struktura DNA; Binding Sites; lidé; homologní rekombinace; Homologous Recombination; Humans; Protein Multimerization; RecQ Helicases; Protein Structure, Tertiary